The MAXIMA Experiment: Latest Results and Consistency Tests - Stompor, R; Hanany, S; Abroe, M; Borrill, J; Ferreira, P; Jaffe, A; Johnson, B; Lee, A; Rabii, B; Richards, P; Smoot, G; Winant, C; et al. (2003)
The MAXIMA cosmic microwave background anisotropy experiment had a significant impact on cosmology. Results from the program have played a significant role in determining the geometry of the universe, given strong supporting evidence to inflation, and, in combination with other astrophysical data, showed that the universe is filled with dark matter and energy. We present a subset of the internal consistency checks that were carried out on the MAXIMA-1 data prior to their release, which demonstrate that systematics errors were much smaller than statistical errors. We also discuss the MAXIMA-2 flight and data, compare the maps of MAXIMA-1 and -2 in areas where they overlap and show that the two independent experiments confirm each other. All of these results demonstrate that MAXIMA mapped the cosmic microwave background anisotropy with high accuracy